Urgensi Pengaturan Tindakan Pelarangan Penjualan Produk Hasil Pelanggaran Rahasia Dagang Berdasarkan Perbandingan Undang-Undang Nomor 30 Tahun 2000 Tentang Rahasia Dagang dan Directive (EU) 2016/943 - Aurelia Salsabilla Novalika; Ranti Fauza Mayana; Rika Ratna Permata (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2025)
Trade secret is one of the Intellectual Property Rights (IPR) protected by the Law No. 30 Year 2000 on Trade Secrets. However, the Trade Secret Law has not regulated in detail the act of prohibiting the sale of products resulting from trade secret infringement. Therefore, the purpose of this research is to analyse the reasons for the urgency of regulating the act of prohibiting the sale of products resulting from violations of Trade Secrets based on the Trade Secrets Act, and to explore the regulation of temporary determination of the sale of products resulting from violations of Trade Secrets based on the Trade Secrets Act and Directive (EU) 2016/943. This research uses normative law and comparative law methods with descriptive analytical research specifications. The research was conducted by comparing the laws. The data collection technique used is literature review. Based on the results of the research, it is concluded that the provisions of the Trade Secrets Law regarding injunction in Article 11 are still not detailed enough to provide legal certainty. This is different from the case of Directive (EU) 2016/943, which has regulated the provisions of interim injunction quite comprehensively. In this case, Indonesia can use Directive (EU) 2016/943 as one of the references to complete the provisions of the Indonesian Trade Secrets Law.